The Effect of Selenium Against Cadmium-Induced Nephrotoxicity in Rats: The Role of the TRPM2 Channel - Ömer Faruk Keleş; Mehmet Hafit Bayir; Hacı Ahmet Çiçek; Adem Ahlatcı; Kenan Yıldızhan (Toxics, 2025)
This study investigated the protective effect of selenium (Se) in a cadmium (Cd)-induced nephrotoxicity model in rats and the role of the TRPM2 channel in this mechanism. For this purpose, Cd (25 mg/kg orally), Se (0.5 mg/kg i.p.), and 2-aminoethoxydiphenyl borate (2-APB), a TRPM2 channel antagonist, (3 mg/kg i.p.) were administered to rats every day for 5 days. At the end of the study, kidney tissues were analysed using histological and biochemical methods. A histopathological examination revealed congestion, tubular degeneration, necrosis, and glomerular adhesion in the Cd group. However, these lesions were significantly reduced in the Cd + Se and Cd + 2-APB groups, while the Cd + Se + 2-APB group showed a histological appearance similar to the control group. Immunohistochemical analysis revealed that Caspase-3, Bax, and TRPM2 expression was higher in the Cd group, while these levels were lower in the Se and 2-APB treatment groups (p < 0.05). Among the groups that received Cd, urea, creatinine, TOS, TNF-α, and IL-1β levels were at the highest level in the Cd group, while TAS level was at the lowest level (p < 0.05). The Se and 2-APB treatment modulated these parameters; however, Se + 2-APB treatment reduced urea, creatinine, TOS, TNF-α, and IL-1β levels to the lowest level compared to the Cd groups and brought the TAS level closer to the control group (p < 0.05). These findings indicated that targeting TRPM2 channel inactivation together with the selenium treatment could alleviate Cd-induced nephrotoxicity.